2019
DOI: 10.1017/mdh.2019.1
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Politics in Twentieth-Century France and Britain

Abstract: This special issue adopts a comparative approach to the politics of reproduction in twentieth-century France and Britain. The articles investigate the flow of information, practices and tools across national boundaries and between groups of experts, activists and laypeople. Empirically grounded in medical, news media and feminist sources, as well as ethnographic fieldwork, they reveal the practical similarities that existed between countries with officially different political regimes as well as local differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…A comparative study between abortion policies in France and the United Kingdom demonstrated that physicians and anti-abortion activists were the main elements of shaping the social awareness of abortion [ 26 ]. The Society for the Protection of Unborn Children was established in 1967 and it is now the oldest anti-abortion organization worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…A comparative study between abortion policies in France and the United Kingdom demonstrated that physicians and anti-abortion activists were the main elements of shaping the social awareness of abortion [ 26 ]. The Society for the Protection of Unborn Children was established in 1967 and it is now the oldest anti-abortion organization worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Mobilising the press in order to disseminate information, they helped to influence policymakers, but also helped to communicate new knowledge to their patients in private settings. 30 For instance, in England, women doctors such as Helena Wright, Margaret 172 Agata Ignaciuk and Laura Kelly Jackson, Joan Malleson and Gladys Cox, played a significant role in the production and circulation of family planning information there, and to a lesser extent in France, between 1930 and1970. 31 Studies of family planning in European contexts, have similarly shown the importance of male doctors in debates around the contraceptive pill.…”
Section: Activists and Experts In Local And Global Settingsmentioning
confidence: 99%
“…France’s approach to ART must also be contextualized against its historical penchant for pronatalism in contrast to some European counterparts, particularly Britain ( Latham, 1998 , Olszynko-Gryn and Rusterholz, 2019 ). The French bioethics law, first framed in 1994, enshrined what bioethics scholars call the ‘French conservative approach’, which, among other things, limited ART access to heterosexual, cohabitating couples who are medically infertile; prohibited surrogacy; and prescribed strict anonymity in gamete donation.…”
Section: Cross-border and (Sex) Selective Art – Francementioning
confidence: 99%